The Narrative within the Late Gothic Carved Altarpieces of Brabant - Sadarova, Anna A. (Actual Problems of Theory and History of Art, 2019)
The article analyzes the place and significance of narrative scenes in the structure of sculpted altars created in the duchy of Brabant at the end of the 14th — first half of the 16th centuries. This steady predominance of dynamic multi-figure narrative compositions is exactly what distinguishes South Netherlandish works from sculpted altarpieces from other European centers. However, occasionally more or less significant attention was also paid to non-narrative images within Brabantine carved retables, may be, to please the tastes of their customers and buyers originating from very different regions of Europe.The article presents various approaches to explaining such a clear preference for narrative. Most often, the altarpieces include the standardized cycles of the childhood of Jesus, the Passion, the lives of the Virgin Mary and the saints. Becoming a kind of background for the liturgy, they sometimes have a semantic connection with it, but they do not literally illustrate the service. Dynamic sculptural cycles reveal close parallels also with mystery plays. Of great importance for the development of narrative imagery was the spread of religious mysticism and the movement of Devotio Moderna in the Netherlands. Detailed, realistic, emotional scenes answered the arising need for visual support for individual meditation on the events of the New Testament.
Keywords: carved retables; sculpted altarpieces; Netherlandish altarpieces; narrative; Christian iconography; sculpture of Brabant; Late Gothic sculpture; Late Medieval art